2019
DOI: 10.2217/pmt-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

The Contemporary Management of Nonspecific Lower Back Pain

Abstract: Low back pain (LBP) is extremely common and causes an enormous burden on the society. This perspective article aims to provide an evidence-based summary in the field of LBP. More specifically, we aimed to present epidemiological data on cost, diagnosis, prognosis, prevention and interventions for patients with LBP. It is critical that both clinicians and policymakers follow best practices by using high-value care for patients with LBP. In addition, nonevidence-based procedures must be immediately abandoned. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The content of this intervention included videos and animations based on pain education, promotion of physical activity, and general exercises. The pain education component was based on the e-pain intervention developed by Reis et al [12], which had 9 main features: (1) acceptance, (2 and 3) pain education, (4) sleep hygiene, (5) recognition of stress and negative emotions, (6) increased positive coping in lifestyle, (7) exercise, (8) communication, and (9) prevention.…”
Section: Intervention Group: Internet-based Pain Education and Exerci...mentioning
confidence: 99%
See 1 more Smart Citation
“…The content of this intervention included videos and animations based on pain education, promotion of physical activity, and general exercises. The pain education component was based on the e-pain intervention developed by Reis et al [12], which had 9 main features: (1) acceptance, (2 and 3) pain education, (4) sleep hygiene, (5) recognition of stress and negative emotions, (6) increased positive coping in lifestyle, (7) exercise, (8) communication, and (9) prevention.…”
Section: Intervention Group: Internet-based Pain Education and Exerci...mentioning
confidence: 99%
“…The management of chronic musculoskeletal pain is primarily multimodal, with noninvasive and nonpharmacological therapies as first-line options. These therapies include exercise, pain education, psychological, and physical therapies [7][8][9][10][11]. Although these recommendations from clinical practice guidelines are clear and usually do not involve complex programs [12,13], many people do not have access to adequate and affordable treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The buoyancy of the water allows a greater range of motion by supporting body weight, and changing the depth helps to develop resistance [110]. The aquatic environment enables the subject to perform activities that would be difficult or impossible on land, and it has been shown that the optimal exercise strength can be accomplished by controlling the speed of motion in water [111].…”
Section: Hydrotherapymentioning
confidence: 99%
“…The utility of incorporating such behavioral health screenings into chronic pain practices may facilitate increased access to appropriate behavioral health treatment, resulting in reduced pain, improvement in function, and overall quality of life improvement (87). When looking at patients with chronic lower back pain, depression and anxiety were associated with changes in pain disability at one-year follow-up, further encouraging universal screening for both disorders (97). With multidisciplinary pain management becoming more prominent, the evidence supporting CBT as an effective treatment for chronic pain patients should be considered as a possible supplemental intervention in the treatment plan (98,99).…”
Section: Barriers and Opportunities To Clinical Implementationmentioning
confidence: 99%